The Interconnection of Psychological Well-Being and Mental Health: A Comprehensive Review - Kalpeshkumar V. Patel; Dr. Pravinkumar V. Chaudhari (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This research paper explores the intricate relationship between psychological well-being and mental health, emphasizing their importance in achieving holistic health. By reviewing existing literature, analyzing key determinants, and highlighting intervention strategies, this paper provides insights into promoting mental well-being. The study also examines challenges in maintaining psychological health in contemporary society and offers recommendations for future research.